Meningkatkan Kemampuan Penjumlahan Deret ke Bawah Melalui Media Cubaritme pada Peserta Didik Disabilitas Intelektual Ringan (Single Subject Research di Kelas V SLB Serasi Kota Payakumbuh) - Fajriani, Hafiza; Damri, Damri; Iswari, Mega; Arnez, Gaby; Zulpiani, Mardhatillah (Indo-MathEdu Intellectuals Journal, 2025)
Abstract. This research is motivated by the problems encountered in SLB Serasi, Payakumbuh City. A student with Mild Intellectual Disabilities who has difficulty in understanding abstract mathematical concepts, especially in the operation of adding downward series with the technique of storing. This study aims to improve the ability of downward series addition with the technique of storing through the use of concrete learning media in the form of cubarithme. The method used is a single subject experimental research (Single Subject Research) with an A-B design, consisting of two phases: the baseline phase (A) without treatment and the intervention phase (B) with treatment using cubarithme media. Data collected through written tests analyzed using visual graphics. The results of the study showed that cubarithme media was effective in improving students' abilities. In the baseline phase (A), students' abilities remained at 30% for four sessions. After being given intervention (phase B), the abilities increased gradually to 70%, 70%, 80%, 80%, 80%, and 90%. The increase was accompanied by changes in positive data trends and significant stability of results. It can be concluded that this study shows that cubarithme media is able to help students understand the concept of addition in a concrete, simple, and enjoyable way.